ANALISIS PENGARUH FAKTOR EKONOMI MAKRO TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BEI PERIODE 2019-2022 - Safitri Nurul Hikmah; Gista Rismayani; laras pratiwi (LP2M Universitas Perjuangan Tasikmalaya, 2023)
When market participants make a decision to make an investment, one of them looks at the performance of the Composite Stock Price Index, because they can measure or predict the level of profit that will be obtained. Many factors can make the performance of the stock price index fluctuate, which can be influenced by internal and external factors such as inflation, BI interest rates and Exchange Dollar. This study aims to analyze and determine the effect of macroeconomics on the composite stock price index. The method used in this study is a quantitative approach to the type of associative research. Source of data in this study using secondary data sourced from the official website, namely www.bi.go.id, www.bps.go.id, and www.idx.co.id with documentation and library research as a data collection technique. The data processing method uses multiple linear regression with the sampling technique used being a saturated sample. This research consists of Descriptive testing and Hypothesis Testing with SPSS version 29. Based on the results of the study, it was stated that inflation and the dollar exchange had a significant effect on the JCI, while the BI Rate variable had no significant effect on the JCI. Simultaneously Inflation, BI Interest Rate, Dollar Exchange have a significant effect on the JCI. Keywords: BI Interest Rate, Exchange Dollar, Inflation, JCI.